Strategic portfolio analysis according to the cognitive approach: a theoretical framing - Nima Abbas Al-Khafaji; Asfad Murtada Al-Hadithi (Iraqi Journal for Administrative Sciences, 2024)
Thinking about the strategic portfolio has attracted the interest of many thinkers and researchers in the sciences who have adopted strategic thinking as their approach, including financial management, marketing, and operations science. These approaches have enriched the strategic portfolio with analysis and interpretation, each according to its vision. The cognitive approach complements these efforts by providing a unique vision of the strategic portfolio derived from its philosophy, which is based on the role of strategic thinking of top management in analyzing the strategic portfolio, interpreting its movements, and predicting its dimensions, variables, positions, and strategic options. This research focuses on the possibility of relying on the cognitive approach in building the strategic portfolio, attempting to achieve the following scientific contributions: Firstly, it is considered one of the recent research studies that addressed the strategic portfolio with explanation and interpretation—secondly, distinguishing between the dimensions of the strategic portfolio, strategic positions, variables, and strategic options in particular and thirdly, developing expected solutions for the intellectual dilemma formulated by a cognitive model for the strategic portfolio. In light of the points mentioned above, it can be said that this topic falls within the field of strategic management and belongs to the cognitive approach within the framework of mental processes and components of that mind embodied by cognitive abilities and awareness of strategic goals. Based on this, it is generally agreed that the research should provide a theoretical framework for the strategic portfolio according to the cognitive approach.